Magnetocaloric properties and critical behavior of high relative cooling power FeNiB nanoparticles - Chaudhary, V. (2014)
Low cost magnetocaloric nanomaterials have attracted considerable attention for energy efficient applications. We report a very high relative cooling power (RCP) in a study of the magnetocaloric effect in quenched FeNiB nanoparticles. RCP increases from 89.8 to 640 J kg−1 for a field change of 1 and 5 T, respectively, these values are the largest for rare earth free iron based magnetocaloric nanomaterials. To investigate the magnetocaloric behavior around the Curie temperature (TC ), the critical behavior of these quenched nanoparticles was studied. Detailed analysis of the magnetic phase transition using the modified Arrott plot, Kouvel-Fisher method, and critical isotherm plots yields critical exponents of β = 0.364, γ = 1.319, δ = 4.623, and α = −0.055, which are close to the theoretical exponents obtained from the 3D-Heisenberg model. Our results indicate that these FeNiB nanoparticles are potential candidates for magnetocaloric fluid based heat pumps and low grade waste heat recovery.